HOUSING EXPANSION AND LANDSCAPE FRAGMENTATION: A MULTITEMPORAL LANDSCAPE-METRICS ANALYSIS - Rieneke Lusia Evani Sela; Andy Anton Mangopa Malik; Sonny Tilaar; Dwight Viosela Aaron Mambu; Erlangga Nonto (EDUCATIONE, 2026)
Mapanget District is a peri-urban growth area of Manado City where residential development has altered the composition and configuration of land use. This study reanalyzes a consistent 2014, 2019, and 2024 land-use series and uses landscape metrics to distinguish patch proliferation from spatial consolidation. Google Earth imagery was interpreted visually, digitized on screen, processed in ArcMap 10.8, and converted to raster for FRAGSTATS 4.2 analysis. The 2026 map is reported only as a separate descriptive snapshot because its class legend is not equivalent to the 2014-2024 classification. Between 2014 and 2024, residential land increased by 172.82 ha, while plantation and wasteland decreased by 154.80 ha and 37.42 ha, respectively. At the landscape level, Number of Patches increased from 1,152 to 1,530, Patch Density from 21.63 to 28.70 patches per 100 ha, Edge Density from 102.38 to 119.33 m/ha, and Shannon's Diversity Index from 1.22 to 1.27. Residential patches increased from 489 to 747; however, the slight decline after 2019 and the rise in residential Largest Patch Index from 1.44% to 3.29% indicate partial coalescence alongside continued outward expansion. The 2026 snapshot records 1,199.26 ha of settlement and 2,699.91 ha of plantation, but these values are not used to infer a continuous trend. The findings support compact, infrastructure-connected growth and stronger protection of remaining non-built-up land. Interpretation is limited by the absence of an independent accuracy assessment, a harmonized 2026 legend, and a class-to-class transition matrix.